Impact of age on the performance of the ESC 0/1h-algorithms for early diagnosis of myocardial infarction - Boeddinghaus, Jasper; Nestelberger, Thomas; Twerenbold, Raphael; Neumann, Johannes Tobias; Lindahl, Bertil; Giannitsis, Evangelos; Sörensen, Nils Arne; Badertscher, Patrick; Jann, Janina E; Wussler, Desiree; Puelacher, Christian; Rubini Giménez, Maria; et al. (European heart journal, 2018)
Aims: We aimed to evaluate the impact of age on the performance of the European Society of Cardiology (ESC) 0/1h-algorithms and to derive and externally validate alternative cut-offs specific to older patients. Methods and results: We prospectively enrolled patients presenting to the emergency department (ED) with symptoms suggestive of acute myocardial infarction in three large diagnostic studies. Final diagnoses were adjudicated by two independent cardiologists. High-sensitivity cardiac troponin (hs-cTn) T and I concentrations were measured at presentation and after 1 h. Patients were stratified according to age [<55 years (young), ≥55 to <70 years (middle-age), ≥70 years (old)]. Rule-out safety of the ESC hs-cTnT 0/1h-algorithm was very high in all age-strata: sensitivity 100% [95% confidence interval (95% CI) 94.9-100] in young, 99.3% (95% CI 96.0-99.9) in middle-age, and 99.3% (95% CI 97.5-99.8) in old patients. Accuracy of rule-in decreased with age: specificity 97.0% (95% CI 95.8-97.9) in young, 96.1% (95% CI 94.5-97.2) in middle-age, and 92.7% (95% CI 90.7-94.3) in older patients. Triage efficacy decreased with increasing age (young 93%, middle-age 80%, old 55%, P < 0.001). Similar results were found for the ESC hs-cTnT 0/1h-algorithm. Alternative, slightly higher cut-off concentrations optimized for older patients maintained very high safety of rule-out, increased specificity of rule-in (P < 0.01), reduced overall efficacy for hs-cTnT (P < 0.01), while maintaining efficacy for hs-cTnI. Findings were confirmed in two validation cohorts (n = 2767). Conclusion: While safety of the ESC 0/1h-algorithms remained very high, increasing age significantly reduced overall efficacy and the accuracy of rule-in. Alternative slightly higher cut-off concentrations may be considered for older patients, particularly if using hs-cTnI. Clinical Trial Registration: https://clinicaltrials.gov/ct2/show/NCT00470587, number NCT00470587 and NCT02355457 (BACC).
Keywords: troponin; Male; Early Diagnosis; Troponin; Adult; Age Factors; Aged; dospělí; Practice Guidelines as Topic; mužské pohlaví; senioři; Prospective Studies; algoritmy; infarkt myokardu; lidé; ženské pohlaví; Humans; časná diagnóza; senzitivita a specificita; Myocardial Infarction; věkové faktory; Sensitivity and Specificity; Algorithms; Female; lidé středního věku; směrnice pro lékařskou praxi jako téma; Middle Aged; prospektivní studie